Sosialisasi Literature Approach Dalam Peningkatan Kemampuan Komunikasi Bahasa Inggris Menggunakan Perangkat Multimedia di SMA Negeri 2 Prabumulih - Uzer, Yus Vernandes; H, Hermansyah; H, Herlina; Mortini, Asti Veto; M, Marleni; Hidayad, Ferri; Uzer, Yuspar; Jaya, Aswadi (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
Socialization of Literature Approach in Improving English Communication Skills Using Multimedia Devices at Sma Negeri 2 Prabumulih, students are expected to be able to speak English fluently through communicative English conversation training with a 1-hour system. Generally, students only learn basic sentence forms by constructing sentences in English and how to pronounce them in learning conversation, but in this training, we, the lecturers of the DTY FKIP Study Program through Community Service (PKM) activities will provide English learning with the title Socialization of Literature Approach in Improving English Communication Skills Using Multimedia Devices at Sma Negeri 2 Prabumulih, in one day of learning activities (Duration 4 hours of learning).